Laboratory and clinical analysis of the treatment with direct-acting antiviral drugs in patients with hepatitis C (Research, Society and Development, 2022)
Hepatitis C is a disease caused by the HCV virus, whose greatest difficulty in diagnosis is the lack of specificity of symptoms, contributing to chronification and a worse prognosis. The infection affects about 58 million people worldwide. In the last two decades, 265.000 cases were confirmed in Brazil. In 2015, the treatment was optimized after the inclusion of direct-acting antivirals (DAAs) that reduced adverse effects. Objective: to evaluate the clinical and laboratory response of the treatment of hepatitis C with the use of new DAAs. Methodology: cross-sectional, qualitative and descriptive study with a non-probabilistic sample of the medical records of patients with HCV assisted at the CTA/SAE in Santarém - PA, from January 2016 to March 2019. Results: among the 265 medical records, only 45 fit in the inclusion criteria. The Sofosbuvir + Daclatasvir regimen was the most used (44.44%). There was a reduction in hematocrit values ​​and liver enzymes (TGO/TGP), however there was an increase in hemoglobin and platelets. Genotype 1B was the most prevalent. The degree of F4 fibrosis stood out, especially in men. The predominant comorbidity was systemic arterial hypertension. Conclusion: After the inclusion of the 2nd generation of DAAs, there was a reduction in cases of severe anemia, transaminases and thrombocytopenia. In addition, the need for more effective laboratory control of hemoglobin was perceived when there is an association of ribavirin with the therapeutic regimen and the sexual route was the means of contamination in a way opposite to the national data.